Correction: Performance of the national institute of infectious diseases disability scale in HTLV-1-associated myelopathy/tropical spastic paraparesis (Journal of NeuroVirology, (2023), 29, 5, (555-563), 10.1007/s13365-023-01154-y) - Schmidt, Felipe R.; Coutinho, Evandro S. F.; Lima, Marco A.; Silva, Marcus T. T.; Leite, Ana C. C. B.; Fonseca, Igor O. [UNESP]; Araujo, Abelardo Q. C. (Springer Nature, 2023)
In Appendix 1, “Total: ____ (0–31)” should instead read “Total: ____ (10–41).”